Risk factors for exercise-related acute cardiac events. A case–control study. Issue 9 (4th September 2009) - van Teeffelen, W M; de Beus, M F; Mosterd, A; Bots, M L; Mosterd, W L; Pool, J; Doevendans, P A; Grobbee, D E
Abstract : Background: In spite of the benefits of physical activity, exercise may provoke acute cardiac events in susceptible individuals. Understanding risk factors of exercise-related acute cardiac events may identify opportunities for prevention. Methods: A case–control study was conducted to examine determinants of acute cardiac events in athletes. The cases were athletes who suffered an acute cardiac event during or shortly after vigorous exercise. Athletes who visited a hospital because of a minor sports injury were selected as controls. Information on cardiovascular disease, family history of cardiovascular disease, cardiovascular symptoms and other potential risk factors was collected through questionnaires. Results: 57 cases (mean age 41.8 years, range 11–73) and 57 controls (mean age 40.9 years, range 13–68) were included in the study. Athletes with a history of cardiovascular disease were at a markedly increased risk for cardiac events during exercise (OR = 32; 95% CI 7.4 to 143). Smoking (OR 5.9; 95% CI 1.9 to 18), fatigue (OR = 12; 95% CI 1.2 to 118) and flu-like symptoms (OR 13; 95% CI 1.4 to 131) in the month preceding the event were related to acute cardiac events in athletes. Conclusions: Prior cardiovascular disease, smoking, and a recent episode of fatigue or flu-like symptoms are associated with an increased risk of exercise-related acute cardiac events. Athletes and physicians should pay careful attention when these factors exist or occur.